Analysis Politeness Speak On Account TikTok @Iamegamei: Person India, No Vrindavan Or Pridapan - Irma Khilyaturrahmah; Devi Ayu Dwi Romadona; Mirna Layli Dewi; Nurul Karina Ningsih; Asep Purwo Yudi Utomo; Iwan Hardi Saputro; Rossi Galih Kesuma (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language politeness is the values of politeness or ethics when speaking that are contained in the social rules of society. Language politeness plays an important role in communication because in communicating speakers not only pronounce the sounds of the language, but also ensures that the speech can be accepted by speech partners. Therefore, research on linguistic politeness is interesting to do, especially linguistic politeness in social media that is widely accessed by the public, one of which is the TikTok channel. This research was conducted to identify the principles of language politeness in 2 minutes 46 seconds video on @iamegamei's TikTok channel. The video criticizes the labeling of Indians as Vrindavan or Prindapan with negative connotations that are often done by Indonesian netizens. This research method uses descriptive qualitative pragmatic method with observing and note-taking techniques. Then the data is analyzed using a pragmatic equivalent method. From the research that has been conducted, it is found that the obedience and violation of language politeness thimbles. However, thimble violations dominate, causing language impoliteness in the TikTok video of @iamegamei's account.